Pengaruh Motivasi Konsumen Terhadap Kualitas Pelayanan Jasa Pada Usaha Bengkel TKM Service di Panerokan - Syafrudin Syafrudin (LEMBAGA PENELITIAN DAN PENGABDIAN PADA MASYARAKAT STIE-GRAHA KARYA MUARA BULIAN, 2020)
The purpose of this study was to determine the effect of the influence of consumer motivation on the quality of services in the TKM service workshop business in Panerokan. The research method uses descriptive qualitative and quantitative verification to describe each variable and determine the effect of each variable in the formulation of the problem. Data obtained directly from the original source, namely consumers KTM Service workshop in Panerokan using a questionnaire. The analysis technique uses descriptive analysis which is calculated using a Likert scale. Then the calculation is carried out through a simple regression analysis method. The results of the discussion show that (1) The achievement of consumer motivation at the KTM service workshop in Panerokan shows the index value of 372.37 is included in the category of criteria with a high category, meaning that the respondent has strong consumer motivation towards the KTM service workshop in Panerokan due to good service and price. according to the job and the location that is easy to reach and not jammed, this is evidenced by the respondent's answer to the achievements of the 3 indicators and 10 statements on the answers to the questionnaire, (2) The achievement of service quality at the KTM service workshop in Panerokan shows an index value of 364.25 including in the category of criteria with a high category, meaning that the respondent has a strong assessment of the service quality of the KTM workshop service at Panerokan due to good service, and the price is in accordance with the job and the location is easy to reach and not jammed, this is evidenced by the respondent's answer to the achievements of 5 ind ikator and 22 statements on the answers to the questionnaire. From the results of the multiple regression equation, it can be seen that consumer motivation is significantly influenced by service quality. The coefficient of determination (R2) is 0.299 or 29.90% which indicates that between service quality while the remaining 71.10% is influenced by other variables not examined.